Sistem Pendukung Keputusan Penerimaan PKH Menggunakan Metode AHP-ARAS - Hidra Amnur; Debi Indah Syafira; Yulherniwati (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
The Government's Village Fund Family Hope Program (PKH) is a form of social assistance to village communities. One of the villages receiving this assistance is Ampek Angkek District, located in the Agam Regency area. For prospective PKH recipients, an appropriate decision support system is used for accepting PKH candidates. The Analytical Hierarchy Process (AHP) method and the Addative Assessment Ratio (ARAS) method are suitable methods for creating a decision support system for PKH acceptance. The Analytical Hierarchy Process (AHP) method is used to determine the weight value for each data from potential aid recipients, and the Addative Assessment Ratio (ARAS) method is used to rank potential aid recipients according to the weight values that have been obtained using the Analytical Hierarchy Process (AHP) method. The results obtained from manual calculation testing are the same as the system calculation results